The Effect of Different Cooking Techniques and Internal Cooking Temperature Applications on The Oxidative Stability of Hamburger Patties - Şimşek, Azim (Turkish Journal of Agriculture - Food Science and Technology, 2020)
The aim of this study was to investigate the effects of different cooking techniques and internal cooking temperature applications on the oxidative stability of hamburger patties. For this purpose, 4 different cooking techniques (boiling, oven-roasting, grilling and microwave) and 2 different internal cooking temperatures (72°C and 78°C) were used. Microwave cooking caused the highest cooking loss values. The higher cooking loss values were determined as a result of the 78°C internal cooking temperature application. Lower pH values were obtained by microwave cooking. Boiling increased L* and a* values, whereas decreased b* values compared to other cooking techniques. While a* values decreased with storage in hamburger patties, b* and HUE angle values increased. The lower thiobarbituric acid reactive substances (TBARS) and lipid hydroperoxide (LPO) values were determined in samples cooked with microwave or boiling technique. Even though there was no TBARS difference between different internal cooking temperature applications, the higher LPO values were determined in the application of 78°C internal cooking temperature. The results of this study showed that less oxidative changes could be occurred by the use of either microwave or boiling technique in hamburger patty production.